From Adam to Armageddon - White, J. Benton
A uniquely concise book for surveys of the Bible, FROM ADAM TO ARMAGEDDON, 5th Edition offers a clear and readily accessible introduction to the Bible. Reflective of the typical mainstream methods and analyses of contemporary academic religious studies, this book offers your students an even-handed look at both the grand gestures and key nuances of the Bible's text and history, encouraging them to develop their own critical appreciations of the book